Respiratory syncytial virus glycoprotein G impedes CX3CR1-activation by CX3CL1 and monocyte function - Robert Meineke; Ayse Agac; Marie-Christin Knittler; Martin Ludlow; Albert D. M. E. Osterhaus; Guus F. Rimmelzwaan (npj Viruses)
Abstract The soluble form of the Respiratory Syncytial Virus (RSV) G protein (sG) bears resemblance to the chemokine fractalkine (CX₃CL1). Both RSV sG and CX3CL1 possess a mucin-like domain and a CX3C motif, exist in membrane-associated and soluble forms, and bind to the CX₃CR1 receptor expressed on immune and epithelial cells. To explore the biological significance of RSV sG and CX₃CR1 interaction, we produced wild type (WT) and CX₃C motif-deficient (CX3CMut) RSV sG proteins and determined their effects on CX₃CR1 signaling in monocytic cells. Both CX3CMut- and WT RSV sG failed to activate CX₃CR1 signaling directly. However, WT sG competed with CX₃CL1 for CX₃CR1 binding and reduced CX3CL1-induced CX₃CR1-activation, monocyte migration, and adhesion. The CX₃C motif of sG was crucial for competitive blocking of CX3CL1-mediated activation, as CX₃CMut sG did not affect these CX₃CR1 functions significantly. Thus, blockade of CX₃CR1 signaling by sG may allow RSV to dampen host immune responses.